Extending Lean Operating Limit and Reducing Emissions of Methane Spark-Ignited Engines Using a Microwave-Assisted Spark Plug - Vi H. Rapp; Anthony DeFilippo; Samveg Saxena; Jyh-Yuan Chen; Robert W. Dibble; Atsushi Nishiyama; Ahsa Moon; Yuji Ikeda (Journal of Combustion)
A microwave-assisted spark plug was used to extend the lean operating limit (lean limit) and reduce emissions of an engine burning methane-air. In-cylinder pressure data were collected at normalized air-fuel ratios of λ=1.46, λ=1.51, λ=1.57, λ=1.68, and λ=1.75. For each λ, microwave energy (power supplied to the magnetron per engine cycle) was varied from 0 mJ (spark discharge alone) to 1600 mJ. At lean conditions, the results showed adding microwave energy to a standard spark plug discharge increased the number of complete combustion cycles, improving engine stability as compared to spark-only operation. Addition of microwave energy also increased the indicated thermal efficiency by 4% at λ=1.68. At λ=1.75, the spark discharge alone was unable to consistently ignite the air-fuel mixture, resulting in frequent misfires. Although microwave energy produced more consistent ignition than spark discharge alone at λ=1.75, 59% of the cycles only partially burned. Overall, the microwave-assisted spark plug increased engine performance under lean operating conditions (λ=1.68) but did not affect operation at conditions closer to stoichiometric.